Clinical and microbiological characteristics and outcomes of complicated urinary tract infections managed in a hospital-at-home programme: a prospective observational cohort study - Lira Pelari-Mici; Elena Arranz Canales; Alexia Constanza Espiño Álvarez; Eva María Fernández Bermejo; Ángela Sánchez Juez; Victoria Gutiérrez Gómez-Lus; Fernando Ruiz Berraco; Saida Alonso Marrero; Jaime Bustos Carpio; José Curbelo; Eduardo Albers Acosta; Pablo Rodríguez-Cortés (European Journal of Clinical Microbiology & Infectious Diseases, 2026)
Abstract Purpose Complicated urinary tract infections (cUTIs) are a frequent indication for admission to Hospital-at-Home (HaH) and outpatient parenteral antimicrobial therapy (OPAT) programmes. We describe the clinical, urological and microbiological profile, antimicrobial treatment and outcomes of a cUTI cohort managed in a HaH unit, and explored, in an exploratory analysis, factors associated with the 30-day composite of unplanned readmission or death. Methods Prospective observational single-centre cohort of 262 consecutive cUTI episodes managed in a tertiary HaH unit (March 2023-October 2025). Baseline, urological, microbiological, treatment and outcome variables were recorded prospectively. Bivariate comparisons and an exploratory multivariable logistic regression were used to examine associations with the composite endpoint. Results Median age was 79.7 years (Q1-Q3 66.1–87.2); 76.0% had multimorbidity. Escherichia coli was the most frequent isolate (45.4%; 41.2% ESBL-producing, 95% CI 32.7–50.2%), and the overall rate of resistance-mechanism-positive isolates was 30.2% (95% CI 24.9–36.0%). Ertapenem (42.8%) and ceftriaxone (41.2%) were the most frequently used intravenous agents. Clinical cure occurred in 92.0% (95% CI 88.1–94.7%) of episodes and 5.3% (95% CI 3.2–8.8%) required unplanned transfer to conventional care, with no deaths during the HaH episode. Within 30 days, 11.5% of episodes (95% CI 8.1–15.9%) were followed by hospital readmission and 4.2% (95% CI 2.4–7.4%) by death (composite endpoint, 13.4%, 95% CI 9.8–18.0%). In exploratory, hypothesis-generating analyses limited by the small number of events, older age and prior urological manipulation were identified as potential factors associated with the composite endpoint (age: OR 1.05, 95% CI 1.01–1.10; prior urological manipulation: OR 2.98, 95% CI 1.12–7.98), with wide confidence intervals. Conclusion In this single-centre, uncontrolled descriptive cohort, cUTI managed through HaH/OPAT was associated with high clinical cure and low unplanned transfer, despite a substantial burden of ESBL-producing organisms and other resistance-mechanism-positive isolates. Older age and prior urological manipulation emerged as potential markers associated with adverse outcomes, warranting further characterisation in larger, adequately powered cohorts before informing risk stratification at HaH admission.